2022
DOI: 10.1155/2022/2621476
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Influence of Family Sports Games on the Development of Early Communication Skills in Autistic Children

Abstract: With the development of society, the number of autistic children in China is increasing, which not only makes the family’s happiness very low, but also seriously affects the development of teenagers and society. Among the symptoms of autistic children, early childhood communication skills have received extensive attention. In traditional rehabilitation training, with a lack of parents’ participation, most of the training cannot arouse the interest of autistic children, so the treatment effect is not obvious. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%